Fungicides applications through overhead sprinkler irrigation for control of bean rust - Pinto, Nicésio Filadelfo de Almeida; Costa, Ênio Fernandes da (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this work was to evaluate the efficiency of fungicides sprayed through overhead sprinkler irrigation system (fungigation) in bean (Phaseolus vulgaris L.) plants, naturally infected with Uromyces appendiculatus. The fungicides bitertanol, mancozeb, benomyl and iprodione were sprayed in 12 x 12 m plots following the doses (g a.i./ha) of 175, 1600, 350 and 750, respectively. A portable injector of chemical products was used to inject the fungicides, in four applications with seven to ten-day intervals, rate average was 3.4 mm, during six minutes of application. Grain yield expressed in kg/ha, and disease percentage were of 1,550 and 6.6; 1.238,0 and 20.5; 1.358,0 and 26.9; 1.014, and 42.0; and 1.088,0 e 52.2 for the treatments bitertanol, mancozeb, benomyl, iprodione and check without fungicide, respectively. The results showed the viability of the fungigation method and the efficacy of fungicide bitertanol in the control of bean plant rust.